1980
DOI: 10.1111/j.1365-2141.1980.tb05942.x
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of Platelet‐Associated IgG: a Study on 298 Patients with Various Disorders

Abstract: Summary. Platelet‐associated IgG (PAIgG) was studied by a quantitative platelet radioactive anti‐IgG test (PRAT) in 298 patients. At the time of investigation, 171 patients were thrombocytopenic (platelet count <100 × 109/1), 127 had normal platelet counts. Patients fell into the following disease categories: Idiopathic thrombocytopenic purpura (ITP) (N=81), possible ITP (19), acute ITP (9), systemic lupus erythematosus (22), autoimmune haemolytic anaemia of warm‐type (18), systemic blood disease (65), liver d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(42 citation statements)
references
References 20 publications
(5 reference statements)
2
40
0
Order By: Relevance
“…Similar PAIgG and platelet levels following splenectomy are commonly found in ITP patients, in whom the thrombocytopenia is responsible for the autoimmune mechanism mediated by a specific IgG bound to platelet membrane proteins [24,25] . There exist controversies regarding the clinical significance of PAIgG in pathogenesis of thrombocytopenia in the patients with liver disease [7,14,29,30] . Two studies on partial splenic artery embolization in patients with hypersplenism clearly confirmed an immunological mechanism mediated by PAIgG-induced thrombocytopenia accompanying liver cirrhosis [7,14] .…”
Section: Sekiguchi T Et Al Autoimmune Thrombocytopenia In Hcv-relatementioning
confidence: 99%
“…Similar PAIgG and platelet levels following splenectomy are commonly found in ITP patients, in whom the thrombocytopenia is responsible for the autoimmune mechanism mediated by a specific IgG bound to platelet membrane proteins [24,25] . There exist controversies regarding the clinical significance of PAIgG in pathogenesis of thrombocytopenia in the patients with liver disease [7,14,29,30] . Two studies on partial splenic artery embolization in patients with hypersplenism clearly confirmed an immunological mechanism mediated by PAIgG-induced thrombocytopenia accompanying liver cirrhosis [7,14] .…”
Section: Sekiguchi T Et Al Autoimmune Thrombocytopenia In Hcv-relatementioning
confidence: 99%
“…PAIgG has been demonstrated to be inversely proportional to the platelet count and to the mean platelet lifespan (Dixon et al, 1975;Mueller-Eckhardt et al, 1980;Panzer et al, 1986;Nieminen, 1992;Movahed Shariat Panahi et al, 1994). PA-IgG is known to consist mostly of subclasses IgG1 and IgG3 (von dem Taaning & Petersen, 1988;Tijhuis et al, 1991).…”
Section: Platelet Antibodiesmentioning
confidence: 99%
“…Moreover, increased PA-IgG has been reported in varying proportions of patients with thrombocytopenia that is presumably not of immunological origin (Helmerhorst et al, 1982b;Kelton et al, 1982). With the quantitative platelet radioactive antiglobulin test, Mueller-Eckhardt et al (1980) demonstrated large amounts of PA-IgG in patients with systemic blood diseases, such as leukaemias or lymphomas and hepatic or infectious disorders. Warner et al (1999) Movahed Shariat Panahi et al, 1994).…”
Section: Pa-igg In Patients Of Different Groupsmentioning
confidence: 99%
See 2 more Smart Citations